Conformational Analysis of Electron Deficient Substituted Mesocyclic 1,4-Cyclodithioethers by ab initio Calculations - AMIRI*, RAHEBEH; HAGHDADI†, MINA; ATTARHAMIDI, MAHBOBEH (Asian Journal of Chemistry, 2009)
Ab initio Hartree-Fock calculations at the HF/6-31G* level of theory for geometry optimization, MP2/6-31G*//HF/6-31G* and B3LYP/6-311G(2df,p)//HF/6-31G* levels for a single point total energy calculation are reported for the important energy minimum conformers of trans and cis isomers of 2,3-diacetyl-1,4-dithiane (1), 2,3-diacetyl-1,4-dithiepane (2) and 2,3-diacetyl- 1,4-dithiocan (3). According to the HF/6-31G* calculations the trans di-equatorial of 2 and 3 are the most stable conformers but the cis form of 1 is more stable than the others.